Watermarks in Banjar Religious and Literary Manuscripts: A Historical and Codicological Study: Cap Kertas (Watermark) dalam Naskah-Naskah Keagamaan dan Sastra Banjar: Kajian Sejarah dan Kodikologi - Sabirin, Muhammad (Indonesian Journal of Islamic History and Culture, 2026)
This study identifies the variety of watermarks, traces their origins and production periods, and analyzes the role of watermarks in Banjar manuscripts to understand the history of manuscript. Employing historical and codicological approaches, data were collected through literature reviews and direct observation of manuscripts held by the National Library of the Republic of Indonesia and the South Kalimantan Regional Library, supplemented by data from the Katalog Naskah Nusantara Indonesia Tengah. Findings reveal that the Pro Patria watermark predominates, followed by Lion Concordia and Tre Lune. Of the 15 manuscripts and 2 archival records examined, two manuscripts and one archive lacked watermarks but exhibited distinct chain and laid lines. Furthermore, three manuscripts contained two different watermarks within a single volume, and countermarks were identified in eight manuscripts. These results diverge from the Katalog Naskah Nusantara Indonesia Tengah, which is dominated by the Man in the Moon watermark. Correlation analysis indicates a social stratification regarding access to high-quality paper. Out of 40 religious manuscripts, only five lacked watermarks. Conversely, of the 32 literary manuscripts, only six featured watermarks all of which were related to the chronicles of the Banjar Kingdom (Hikayat Banjar). These findings suggest that during that period, the intellectual and political elite maintained exclusive access to high-quality imported paper, reflecting the influence of royal patronage on the selection of writing media. In contrast, literary manuscripts copied by the general public utilized only unwatermarked paper.